2015
DOI: 10.1111/sode.12153
|View full text |Cite
|
Sign up to set email alerts
|

Mother Emotion, Child Temperament, and Young Children's Helpless Responses to Failure

Abstract: Young children differ in their responses to failure, displaying mastery or helpless behavior patterns. We examine the moderating role of child temperament on the association between parent warmth/negativity and children's helpless responses to failure. Regarding temperament, we focus on tendencies to experience interest and sadness because they entail task engagement and withdrawal, respectively. We measured mother (n5150) expressions of positive and negative emotion during a teaching task, assessed temperamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Longitudinal research during the past decade also demonstrated specificity in warmth processes. With young children, maternal warmth was associated with less child helplessness during a teaching task, but only when children scored high on sadness (Smiley, Tan, Goldstein, & Sweda, ). This finding suggested that mothers were showing warmth when their children demonstrated a need for support.…”
Section: Strengths In Familiesmentioning
confidence: 99%
“…Longitudinal research during the past decade also demonstrated specificity in warmth processes. With young children, maternal warmth was associated with less child helplessness during a teaching task, but only when children scored high on sadness (Smiley, Tan, Goldstein, & Sweda, ). This finding suggested that mothers were showing warmth when their children demonstrated a need for support.…”
Section: Strengths In Familiesmentioning
confidence: 99%
“…We reasoned that a low number of strategies named during a solvable puzzle, following the experience of repeated failure to complete unsolvable puzzles, would capture diminished effort by children who respond to failure with maladaptive cognitions about the self and the task. A different version of this task, modified for younger children, has been used to generate similar indices of behavioral helplessness and shown to be unassociated with lower child cognitive competence or maternal education (i.e., factors contributing to puzzle-solving proficiency; Smiley, Buttitta, et al, 2016; Smiley, Tan, Goldstein, & Sweda, 2016). In our sample, puzzle strategy use decreased significantly from pre- to postchallenge, t (136) = 5.71, p < .001; 56% of the sample showed a decrease in strategy use by at least one strategy, and 23% of the sample showed a decrease in strategy use by at least two strategies.…”
Section: Methodsmentioning
confidence: 99%
“…School-aged children experience a variety of discrete emotions including excitement, shame, and embarrassment when encountering challenges (Heyman et al, 1992; Lewis et al, 2010; Smiley et al, 2016). Emotional responses like these can be measured via self-assessment, observation, or neurophysiological markers (Zeman et al, 2007) and can be more generally understood in terms of two dimensions: emotional arousal (i.e., the intensity of an emotion) and emotional valence (i.e., the pleasantness or unpleasantness of an emotion; Barrett & Russell, 1999).…”
Section: Mother–child Dyadic Responses To Challenging Situations In M...mentioning
confidence: 99%
“…A moderate amount of targeted parental control (e.g., giving instructions only when the child desires assistance) could be perceived by children as supportive “controlling guidance” that reflects a sensitive response to a child’s request for help (Chua et al, 2014). Indeed, responses like these could help children cope with helplessness and anxiety (Nanda et al, 2012; Smiley et al, 2016). However, limited work has been conducted on the relation between children’s perceptions of challenge and parents’ behavior; controlled laboratory paradigms are preferable in order to delineate factors that affect these responses.…”
Section: Mother–child Dyadic Responses To Challenging Situations In M...mentioning
confidence: 99%